A probabilistic resource estimation and semi-reservation scheme forflow oriented multimedia wireless networks. - Kuo, Geng-Sheng (IEEE Communications magazine)
Currently, multimedia is urgently expected in wireless networks. One of the most important and complicated issues is quality of service guarantees in third-generation wireless networks. The purpose of this article is to propose a probabilistic resource estimation and semi-reservation scheme in considering the probability of real usage made by the mobile host. This scheme can efficiently improve the connection blocking probability, connection dropping probability, and bandwidth utilization